1964
DOI: 10.1111/j.1476-5381.1964.tb02047.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Central Depressant Drugs Upon Acetylcholine Release

Abstract: Several central depressant and other drugs have been examined for their effects upon acetylcholine release from the stimulated, perfused cat superior cervical ganglion and rat isolated phrenic nerve-diaphragm preparations. The acetylcholine released was assayed biologically. Amylobarbitone sodium, chloral hydrate, trichloroethanol, methylpentynol, methylpentynol carbamate, paraldehyde, procaine hydrochloride and troxidone reduced the presynaptic release of acetylcholine from the ganglion. They also exhibited a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
1
2

Year Published

1965
1965
1987
1987

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 41 publications
2
37
1
2
Order By: Relevance
“…These compounds shared none of the three properties of the Group A drugs and therefore repetitive stimulation would be expected to have no effect on the degree of block. Methylpentynol carbamate appears in Group C and it is interesting to note that Marley & Paton (1959) have reported that it has a ganglion-stimulant action in the perfused ganglion of the cat, a finding confirmed by Matthews & Quilliam (1964). The reversal by repetitive stimulation of the block of transmission of single impulses produced by adrenaline (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…These compounds shared none of the three properties of the Group A drugs and therefore repetitive stimulation would be expected to have no effect on the degree of block. Methylpentynol carbamate appears in Group C and it is interesting to note that Marley & Paton (1959) have reported that it has a ganglion-stimulant action in the perfused ganglion of the cat, a finding confirmed by Matthews & Quilliam (1964). The reversal by repetitive stimulation of the block of transmission of single impulses produced by adrenaline (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…This effect occurred at concentrations of pentobarbitone comparable to those required for the maintenance of general anaesthesia. Later Matthews & Quilliam (1964) showed that the closely related barbiturate, amylobarbitone, depressed the release of acetylcholine in response to nerve stimulation. Barbiturates also depress the sensitivity of sympathetic ganglion cells to exogenously applied nicotinic agonists (Nicoll & Iwamoto, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Local anaesthetics are known to depress acetylcholine output from cholinergic nerves in relatively low concentrations (Harvey, 1939;Furukawa, 1957;Straughan, 1961 ;Matthews & Quilliam, 1964;Paton & Thomson, 1964) and also inhibit the output of vasopressin from neurohypophyses stimulated electrically (Haller, Sachs, Sperelakis & Share, 1965). The only explanation that has been offered for these effects is that the local anaesthetics may block impulse propagation in the terminals.…”
Section: Discussionmentioning
confidence: 99%